Comparison of the C-mediating killing activity and C-activating properties of mouse monoclonal and polyclonal antibodies against Trypanosoma cruzi - T. L. Kipnis; D. V. Tambourgi; M. J. M. Alves; W. Dias da Silva (Mediators of Inflammation)
A Mouse polyclonal antiserum against Trypanosoma cruzi or its IgG and IgM fractions and five monoclonal antibodies (two IgM, two IgG1 and one IgG2a) recognize and combine with membrane components of trypomastigote forms of the parasite as revealed by immunofluorescence. Although all these antibodies sensitize trypomastigotes and prepare them to activate the complement (C) system, as measured by consumption of total C, C4, B and C3, only the polyclonal antiserum or its IgG, IgM and Fabμ fragments were able to induce trypanosome lysis by the alternative C pathway.